Accountability Dilemma, Burnout, and Coping Mechanisms Among Working Accounting Postgraduate Students: A Phenomenological Study - Yayah Maudy Limbangtasi; Syafika Marzuka; Ulfa Melati; Syarifuddin (LP2M IAIN Palopo, 2026)
This study aims to explore and construct the lived experiences of accounting postgraduate students who simultaneously engage in full-time employment, focusing on accountability dilemmas, burnout, and coping mechanisms. Using an interpretive paradigm and a phenomenological approach, this research captures the subjective experiences of seven informants through in-depth interviews. Data were analyzed using thematic phenomenological analysis to uncover the essential meanings (eidos) underlying participants’ experiences. The findings reveal that working postgraduate students experience dual-role conflicts characterized by time fragmentation, competing priorities, and overlapping accountability demands between academic and professional environments. Accountability is not merely perceived as a formal obligation but evolves into a moral responsibility, intensifying internal pressure to maintain performance in both domains. This condition leads to multidimensional burnout, including emotional exhaustion, mental fatigue, and physical strain, often manifesting as invisible suffering. Furthermore, the study identifies a tendency toward toxic productivity, where individuals persistently sustain performance despite declining well-being. To cope with these pressures, participants develop diverse coping strategies, including structured time management, social adjustment, emotional regulation, and meaning-focused coping grounded in spiritual values. These strategies function not only as stress management tools but also as mechanisms for sustaining resilience and negotiating personal meaning. The study concludes that the experience of working while studying represents an ongoing existential negotiation between responsibility, identity, and self-preservation within competing institutional demands.